Fluid flow simulation of industrial fixed bed mixed-flow grain dryer using k-ω SST turbulence model - Visconcini, Anderson Rodrigo; Andrade, Cid Marcos Gonçalves; Costa, Alexandre Marconi de Souza (International Journal of Agricultural and Biological Engineering, 2021)
The fluid dynamics analysis on industrial, mixed-flow grain dryers with fixed bed using computational techniques is necessary to assist the design of such equipment contributing to cost reduction in the dryer projects and agricultural drying operations that involve the production of grains in the world. This study presents a Computational Fluid Dynamic (CFD) solution for air flow analysis in an industrial dryer. The air flow at the inlet and outlet of the dryer was investigated using the k-ω SST turbulence model. The dryer region with soybean was considered as a laminar porous medium flow in the permanent and isothermal regime, having for the model a simplified geometry with the tower considered as a porous medium and the air inlet and outlet as a turbulent fluid domain. The flow was treated with a permanent and isothermal regime. Dryer flow and pressures were used according to design parameters. To validate the k-ω SST turbulence model, the velocity profile at the dryer inlet was obtained experimentally, which presented results with good agreement between the numerical and the experimental model. The model obtained satisfactory results of the computational validation of the air flow in the dryer with good convergence requiring a minimum of computational effort, being suitable for the simulation of industrial-scale dryers, as to its air flow through a tower, operating with fixed bed soybean in the steady and isothermal regime. Keywords: computational methods, fixed bed, porous medium, soybean dryer, turbulent flow DOI: 10.25165/j.ijabe.20211402.5321 Citation: Visconcini A R, Andrade C M G, Costa A M S. Fluid flow simulation of industrial fixed bed mixed-flow grain dryer using k-ω SST turbulence model. Int J Agric & Biol Eng, 2021; 14(2): 226–230.